Prognostiese evaluasie van die N.S.A.G. - Toets ten opsigte van sukses van eerstejaaruiniversiteitstudente - Swiegers, D.J. (University of Pretoria, 2013)
Dissertation (MA)--University of Pretoria, 1963.